Robust Application Level QoS Management in Service-Oriented Systems - LIANG, Qianhui (Althea) (Institutional Knowledge at Singapore Management University, 2008)
Quality of Service (QoS) in Web services has been an active research topic in service-oriented applications. This paper presents a framework for application-level QoS management in services-oriented systems using AI techniques. More precisely, we introduce a management layer, called the business end-user QoS management layer, to be in charge of QoS management at the application level of the applications based on composite Web services. This management layer relies on the measurements against various QoS dimensions of constituent Web services of such applications. A robust algorithm is applied in order to select the most suitable Web services that satisfy the user QoS requirements in a robust way. The effectiveness of the proposed algorithm for this layer of QoS management is demonstrated by experimental results.